Gastric cancer: An approach to its risk factors and prevention (Research, Society and Development, 2024)
This research aimed to describe the main risk factors, in addition to the main ways to prevent gastric cancer. An integrative literature review was carried out, using articles found in the PubMed, SciELO, Lilacs and Sciencedirect databases, selecting works published between 2013 and 2023, in Portuguese, English and Spanish, considering the following descriptors: “factors risk”, “prevention”, “gastric cancer” and “Helicobacter pylori”. A total of 421 works were found, and 20 works were finally selected for study. The development process of gastric cancer is modulated by several conditions, with the main risk factors being: age, consumption of smoked foods, a positive family history and H. pylori infection. Gastric cancer prevention can be divided into primary and secondary. Primary prevention seeks to minimize risk factors, while secondary prevention focuses on early diagnosis. Therefore, knowledge of risk factors and preventive factors are important strategies for controlling the incidence of gastric cancer.